Layer specific and general requirements for ERK/MAPK signaling in the developing neocortex - Lei Xing (eLife, 2016)
Aberrant signaling through the Raf/MEK/ERK (ERK/MAPK) pathway causes pathology in a family of neurodevelopmental disorders known as 'RASopathies' and is implicated in autism pathogenesis. Here, we have determined the functions of ERK/MAPK signaling in developing neocortical excitatory neurons. Our data reveal a critical requirement for ERK/MAPK signaling in the morphological development and survival of large Ctip2+ neurons in layer 5. Loss of Map2k1/2 (Mek1/2) led to deficits in corticospinal tract formation and subsequent corticospinal neuron apoptosis. ERK/MAPK hyperactivation also led to reduced corticospinal axon elongation, but was associated with enhanced arborization. ERK/MAPK signaling was dispensable for axonal outgrowth of layer 2/3 callosal neurons. However, Map2k1/2 deletion led to reduced expression of Arc and enhanced intrinsic excitability in both layers 2/3 and 5, in addition to imbalanced synaptic excitation and inhibition. These data demonstrate selective requirements for ERK/MAPK signaling in layer 5 circuit development and general effects on cortical pyramidal neuron excitability.